2012
DOI: 10.9724/kfcs.2012.28.1.017
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Application of Indigenous Pigmented Rice for Garaedduk Adapted with Mechanically Impacting Technology

Abstract: The present study was performed to expand the application of mechanically impacting technology reported in our previous studies. Several parameters were analyzed to research Korean indigenous pigmented rice. The proximate composition of Korean indigenous rice was the following; 12.0-13.4% moisture, 74.1-77.3% carbohydrate, 6.8-8.7% crude protein, 1.68-3.25% crude lipid, 0.78-1.38% crude ash, with a 6.6-7.07 pH value. The phenolic compound content of red rice was twice that of black rice. Moreover, antioxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Rice cake is a popular dessert and can be consumed as a convenience food. Recently, studies on rice cakes have been focused on manufacturing techniques or freezing methods to inhibit retrogradation and minimize changes in food quality during storage (Han et al, 2012;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rice cake is a popular dessert and can be consumed as a convenience food. Recently, studies on rice cakes have been focused on manufacturing techniques or freezing methods to inhibit retrogradation and minimize changes in food quality during storage (Han et al, 2012;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The desirable qualities of Garaetteok include a low retrogradation, little loss of solids during cooking, and a good mouth feeling after cooking. [2][3][4][5] The processing conditions, including moisture content, [6] the number of extrusions, [7] and flour milling, [8,9] and rice variety [10] are factors that affect the quality of Garaetteok. It has been reported that the processing conditions that yield Garaetteok of the most suitable quality are 40% moisture content (rice flour: water = 1: 0.4), rice soaking time of 8-10 h, and flour steaming time of 40 min.…”
Section: Introductionmentioning
confidence: 99%